(3MGTjI Ydi TQM GdbdGFO ef ebOeI GdHMQs - (3YHO Gddg Hf eMeO Hf CHj GdbGSe GdfMQj,J (B877 (3g` s ((3eMi Hf CMeO Hf MSjf s)
(3ChdgG (B:s
(3MeOkG dc jG ef hjG ef cdGeg GdaUd ai GdcdGe hcGf TQM GdbdGFO ef ebOeg GdHMQ ddbGVi bO deY fhQ GMbjbg CLHJ Cf CcJH Ydjg gPg GdMhGTi s
(3BNQgG (B:s
(3hfMf dGfOYi C, Pdc CQLM ef GdCeQ HGdeYQha hEfeG fQjO fYfi MOjK CHj KYdHI GdMKfi aajeG PcQfG JGeg dg HGdebUhO hGajI JeJ GdMGTjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3efbhdg Yf fSNI HNW GdeDda cJHJ (B1046(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdJhMjO hGdedd hGdfMds